Interpolation Based Data Filling Approach of Incomplete Fuzzy Soft Set - Sudip Kumar Adhikari, Amalendu Si, Anup Kumar Kolya, (International Journal of Scientific Research and Management (IJSRM), 2017)
Soft set theory which deals with vagueness and uncertainties are based on complete information. However, in practical problems, incomplete information also widely exists. The missing data in incomplete fuzzy soft set reduces the utilization of fuzzy soft set. In this paper, a new concept is introduced to estimate the missing data by the other incomplete fuzzy soft sets which improve the performance and importance of the incomplete soft set. The missing data is evaluated by the experts’ observation using the interpolate relations among same properties and same object. An illustrative example shows that the accuracy and feasibility of estimated missing data is much better than the earlier reported techniques in a real application